PENGARUH EMAIL MARKETING DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK TONER PRINTER DI PT BINTANG SETYA MEDIA CIPUTAT - Daryati Daryati; Ali Mubarok (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the influence of Email Marketing and Brand Awareness on Purchase Decisions at PT Bintang Setya Media Ciputat. The data analysis in this study was conducted using SPSS version 25. The research method employed was a quantitative approach. The population consisted of 700 consumers of PT Bintang Setya Media Ciputat, based on sales data from the 2020–2024 period. Using the Slovin formula with a 10% margin of error, a sample of 88 respondents was obtained. The data analysis techniques included validity testing, reliability testing, classical assumption testing, descriptive analysis, simple linear regression analysis, multiple linear regression analysis, correlation coefficient testing, coefficient of determination testing, t-test, and F-test. The results showed that Email Marketing (X1) had a positive and significant effect on Purchase Decisions (Y) with a coefficient of determination value of 14.7%. The hypothesis testing result indicated that the t-value was greater than the t-table value (3.855 > 1.987), therefore H01 was rejected and Ha1 was accepted. The partial correlation coefficient test between Brand Awareness (X2) and Purchase Decisions (Y) produced a correlation coefficient of 0.454, indicating a moderate level of relationship between the two variables. The coefficient of determination was 20.7%, while the remaining 79.3% was influenced by other factors outside this study. The partial hypothesis testing (t-test) for Brand Awareness (X2) on Purchase Decisions (Y) showed that the t-value was greater than the t-table value (4.732 > 1.987), with a significance value of 0.000 < 0.05. Furthermore, the simultaneous hypothesis testing (F-test) of Email Marketing (X1) and Brand Awareness (X2) on Purchase Decisions (Y) indicated that the F-value was greater than the F-table value (14.865 > 2.10), with a significance value of 0.000 < 0.05. Therefore, H03 was rejected and Ha3 was accepted, meaning that Email Marketing and Brand Awareness simultaneously have a positive and significant effect on Purchase Decisions.